Differences in the Long-term Impact of the COVID-19 Pandemic on the Mental Health and Professional Quality of Life of Resident and Specialist Physicians - Delle Donne, Valentina; Massaroni, Valentina; Ciccarelli, Nicoletta; Borghetti, Alberto; Ciccullo, Arturo; Baldin, Gianmaria; Giuliano, Gabriele; Dusina, Alex; Visconti, Elena; Tamburrini, Enrica; Di Giambendetto, Simona (La Medicina del Lavoro, 2023)
Background: The COVID-19 pandemic created an extremely difficult situation for healthcare workers (HCWs) worldwide. We aimed to compare the mental health and professional quality of life of residents and specialist physicians in a cohort of Italian HCWs caring for patients with COVID-19 about two years after the start of the COVID-19 pandemic. Methods: In November 2021, an online survey investigating the emotional states of depression, anxiety, stress, compassion satisfaction and compassion fatigue was administered to HCWs (N= 78) at the Fondazione Policlinico Universitario A. Gemelli IRCCS, Rome. Results: Our findings suggest that from 5 to 20% of our cohort of HCWs still showed the effects of the adverse psychological impact of the pandemic and more than half of them experienced medium levels of compassion fatigue as well as a medium level of compassion satisfaction. Our results also show that those with fewer years of clinical practice might be at greater risk of burnout (p= 0.021), anxiety and stress symptoms (both ps= 0.027) and might develop a lower level of compassion satisfaction (p=0.018). Moreover, the factors that potentially contribute to poor mental health, compassion fatigue and compassion satisfaction seem to differ between residents and specialist physicians. Conclusions: This overview presents one of the first pictures of the long-term effects of the pandemic on the mental health and professional quality of life of an Italian sample of HCWs. Moreover, it also helps identify professionals who are most in need of support and emphasises the importance of improving the psychological and professional wellbeing of these individuals especially during a pandemic-like crisis with long lasting effects.